Elastostatic analysis of underground openings by boundary element method - Zarco, Mark Albert Hofilena
This study attempts to present a boundary element method based on the general displacement discontinuity problem for elastostatic analysis of underground openings. The fundamental solution adopted considers an elastic halfplane. The formulation of the numerical method is discussed.